Metafilozofia Władimira Erna - Herbich, Tomasz (Człowiek i Społeczeństwo, 2022)
Vladimir Ern is often seen as a philosopher that focused mainly on defining the characteristic features of Russian philosophy. When his philosophical works are interpreted in such a way, the biggest stress is being put on the fact that he formulated a certain idea of national philosophy, which was then transformed by him into a kind of national ideology during the World War I. The article tries to show, that Ern should be treated first of all as an author who considered metaphilosophical issues (and that this fact distinguishes him from the majority of the philosophers of Russian religiousphilosophical renaissance, who were mainly interested in solving the metaphysical issues). He focused on metaphilosophy because he was convinced, that philosophy is a field of the battle between two notions of the essence of philosophical knowledge which exclude one another. Seen as such, his philosophy should be interpreted as an attempt to find a proper way in philosophy and to reject the wrong way. The authentic way, which gives a correct answer to the question concerning the essence of philosophical knowledge, was seen by him in Christian Platonism. He tried to show, that in the works of Plato can be found a certain theory of the spiritual development of man, which is at the same time a genuine epistemology that shows the way of true philosophical knowledge.